2001
DOI: 10.1016/s0969-2126(01)00661-x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Imidazole Glycerol Phosphate Synthase

Abstract: This is the first structure in which all the components of the ubiquitous (beta/alpha)(8) barrel fold, top, bottom, and interior, take part in enzymatic function. Intimate contacts between the barrel domain and the glutaminase active site appear to be poised for crosstalk between catalytic centers in response to substrate binding at the cyclase active site. The structure provides a number of potential sites for inhibitor development in the active sites and in a conserved interdomain cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
83
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 39 publications
(1 reference statement)
3
83
0
Order By: Relevance
“…The barrel exhibits a twofold repeat arrangement, (␤␣) [1][2][3][4] and (␤␣) [5][6][7][8] , with two symmetrically related helical insertions between ␤1 and a1 and between ␤5 and ␣5 (Fig. 1b) that suggest this ␤-barrel protein may have evolved by gene duplication similar to what has been suggested for the barrel structures of HisA and HisF (24).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The barrel exhibits a twofold repeat arrangement, (␤␣) [1][2][3][4] and (␤␣) [5][6][7][8] , with two symmetrically related helical insertions between ␤1 and a1 and between ␤5 and ␣5 (Fig. 1b) that suggest this ␤-barrel protein may have evolved by gene duplication similar to what has been suggested for the barrel structures of HisA and HisF (24).…”
Section: Resultsmentioning
confidence: 88%
“…Channeling processes are particularly advantageous over the free diffusion of reaction products through the bulk solvent because they can protect chemically labile intermediates from breakdown, prevent loss of nonpolar intermediates by diffusion across cell membranes, or protect the cell from toxic intermediates. Crystallographic studies on a number of different enzyme systems involved in substrate channeling (3)(4)(5)(6)(7)(8)(9)(10)(11) have revealed important structural factors that mediate intersubunit or interdomain communication and facilitate the efficient transfer of intermediates between distant active sites.…”
mentioning
confidence: 99%
“…Tryptophan synthase from S. typhimurium (58,59), thymidylate synthase/dihydrofolate reductase (TS-DHFR) from Leishmania major (48,60), glutamate synthase from Synechocystis sp. (61), and imidazole glycerol-phosphate synthase from yeast (62,63) are very well characterized examples of bifunctional enzymes that exhibit both channeling and interdomain communications. Domaindomain interactions in these enzymes become evident upon formation of substrate-enzyme complexes (or reaction intermediates) at either of the two reaction centers, which reciprocally and allosterically activate turnover at the other reaction center.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal Stabilization-Structures of several enzymes of the histidine biosynthesis pathway from the hyperthermophile T. maritima have already been determined, including tmHisA (23), tmHisF (23), tmHisH (24), the binary tmHisH-tmHisF complex (24), and the hetero-octameric tmHisG-tmHisZ complex, 2 thereby allowing comparisons with the respective enzyme structures from mesophilic organisms (25)(26)(27)(28). Previous statistical analyses of large structural data sets revealed that the frequency of salt bridges, surface polarity, and structural compactness may be important criteria that affect the structural parameters for thermal stabilization, in general (29,30), and in T. maritima, in particular (31,32).…”
Section: Discussionmentioning
confidence: 99%